(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The project aims in implementing a data transmission we can implement this technology in defence and military areas and also it can be used in many industrial areas. Here LoRa technology is employed because it provides higher level of security. The ability to securely store and transfer sensitive information has proved a critical factor in success in war and business. LoRa technology employs higher level of encryption before sending the data. This project consists of an onboard computer, which consists of number of input and output ports. These onboard computers are commonly termed as micro controllers. The input and output port of the controller are interfaced with different input and output modules depending on the requirements. In other words, micro controller acts as a communication medium for all the modules involved in the project. In this project, we have two sections. Transmitter and Receiver. In Transmitter section, we will be giving a text to be transmitted to the receiver section through Laptop, that data gets encrypted in transmitter section, gets transmitted through LoRa. In Receiver section, the data is received by LoRa and is given to Microcontroller where the encrypted data gets decrypted and gets the original data displayed on Laptop. LCD and Buzzer gives the visual and audible alerts accordingly.